Taxation of e-commerce in Nigeria: treading the global pathway (2016)
Tax policies and legislation arc put in place to ensure adequate taxation, payments and remittances of tax proceeds. Most tax authorities base liability for tax on residence or personal contacts established within the jurisdictions of the tax authorities, while some tax purely on the incomes sourced within the jurisdiction without prejudice to other means or bases of generating tax. However, basing tax on residence seems to be a generally acceptable foundation for levying tax. With the introduction of e-commerce, basing tax on residence or personal links has become a thorny issue in the current tax regime. Many tax revenues arc lost as a result of the inability to tax e-commerce in Nigeria. This article intends to address the challenges created by c-commerce to the tax regime currently in existence and also to review the approaches and efforts made in some jurisdictions and at the international level to address c-commerce taxation with the hope of suggesting ways forward for e-commerce taxation in Nigeria.